Pengaruh Kompres Dingin terhadap Nyeri Kanulasi Arteriovena Fistula (AVF) pada Pasien yang Menjalani Hemodialisis - Azza Husnu Wahda; Dwi Retno Sulistyaningsih; Erna Melastuti (Lembaga Pengembangan Kinerja Dosen, 2025)
Hemodialysis is a medical procedure used to correct blood biochemical abnormalities caused by impaired kidney function, with the aid of a hemodialysis machine. One of the most commonly used accesses in this procedure is the Arteriovenous Fistula (AVF), which is an anastomosis between the artery and vein in the arm or other parts of the body to facilitate the cannulation process. However, during the AVF cannulation procedure, patients often experience pain, which can cause discomfort and anxiety. Cold compresses are one of the non-pharmacological techniques that can be used to alleviate this pain. This study aims to examine the effect of cold compresses on reducing pain during AVF cannulation in hemodialysis patients. This research uses a Quasi-Experimental design with a Pretest-Posttest Control Group Design model, involving 116 hemodialysis patients at RSI Sultan Agung Semarang. Patients were divided into two groups: the intervention group, which received cold compresses, and the control group, which did not receive treatment. Pain intensity was measured before and after cannulation using a visual analog scale (VAS). The results of the study show that the administration of cold compresses significantly reduced pain intensity, with a p-value of 0.000 (< 0.05). In addition, there was a significant difference in effectiveness between the intervention group and the control group, with the same p-value. In conclusion, cold compresses proved to be an effective, simple, safe, and easy-to-apply non-pharmacological intervention to reduce pain in hemodialysis patients during the AVF cannulation procedure. Therefore, the use of cold compresses can be recommended as a method to improve the comfort of hemodialysis patients.